The First External Quality Assurance Laboratory Proficiency Assesment Study of National Antimicrobial Resistance Surveillance System in Turkey - Özakin, Cüneyt; Bayram, Murat; Gürdoğan, Kezban; Perçi̇n Renders, Duygu; Eyi̇gör, Mete; Bayramoğlu, Gülçi̇n; Aktaş, Di̇lber; Göl, Neşe; Şi̇mşek, Hüsni̇ye; Temel, Fehmi̇naz; Gülay, Zeynep; Çöplü, Ni̇lay (LookUs Bilisim A.S., 2018)
© 2018, Refik Saydam National Public Health Agency (RSNPHA).Objective: National Antimicrobial Resistance Surveillance System (NAMRSS) was established aiming to determine and track the percentage of antimicrobial resistance in Turkey, and in order to assure the reliability of the system, an external quality assurance laboratory proficiency assessment was performed in September 2011, for the first time. Methods: Four bacterial strains were sent to 77 participating laboratories. The laboratories were asked to perform the bacterial identification and antimicrobial susceptibility tests (AST) according to standard operating procedures of NAMRSS and Clinical and Laboratory Standards Institute. The results were collected using a web-based questionnaire and the data were analysed using SPSS 15.00. Bacterial identification scoring was defined as ten points when genus and species were accurately defined, eight points when genus was accurate but species was wrong, and zero point when it was misdiagnosed or not reported or contaminated. AST scoring included ten points per antibiotic when the result was correct. Two points were subtracted in case of a minor error (reported as susceptible or resistant when intermediate) and ten points in the case of a major or very major error (reported resistant when susceptable or as susceptible when resistant, respectively) during AST. The threshold value was determined as 70%. Results: From the system, 68 laboratories had sent data and analysed. For Klebsiella pneumoniae, Streptococcus pneumoniae, Enterococcus faecium and Pseudomonas aeruginosa the success percentage for the identification of were 92.6%; 91.2%; 89.7% and 98.5%, respectively; and for AST the median/maximum score that could be achieved were 50/80; 28/50; 40/40 and 60/60, respectively. When the success percentages were classified as ≤69.99%; 70.00%-89.99% and ≥ 90.00%, the distribution of the number of the laboratories were 10; 48; and 10 for the success percentage classes, respectively. Conclusion: In this study, the system was considered reliable.
Keywords: 3. Good health